2004
DOI: 10.1345/aph.1d128
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole in Fungal Keratitis Caused by Scedosporium apiospermum

Abstract: Voriconazole shows promise as an effective alternative to conventional antifungals in the treatment of ScA keratitis. It is available both as oral and intravenous preparations, which is a great advantage in these lengthy infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…28 There is little information in the literature regarding the value of adding oral antifungal medications, despite the fact that it is a common practice among ophthalmologists. Two case reports 29,30 of successful treatment with combined topical, oral, and/or intravenous voriconazole and 1 small randomized clinical trial 31 found a possible improvement in time to ulcer healing among patients treated with oral voriconazole compared with oral itraconazole in Aspergillus species. However, a larger placebo-controlled trial 32 randomizing patients with severe culture-positive fungal ulcers to receive oral ketoconazole vs placebo plus topical natamycin, 5%, did not find a benefit in the group receiving the oral antifungal.…”
Section: Discussionmentioning
confidence: 99%
“…28 There is little information in the literature regarding the value of adding oral antifungal medications, despite the fact that it is a common practice among ophthalmologists. Two case reports 29,30 of successful treatment with combined topical, oral, and/or intravenous voriconazole and 1 small randomized clinical trial 31 found a possible improvement in time to ulcer healing among patients treated with oral voriconazole compared with oral itraconazole in Aspergillus species. However, a larger placebo-controlled trial 32 randomizing patients with severe culture-positive fungal ulcers to receive oral ketoconazole vs placebo plus topical natamycin, 5%, did not find a benefit in the group receiving the oral antifungal.…”
Section: Discussionmentioning
confidence: 99%
“…79 Of note, in many case reports of successful treatment with topical voriconazole, oral and/or intravenous voriconazole was used in conjunction with the topical medication. 80,81 …”
Section: Fungal Keratitismentioning
confidence: 99%
“…Voriconazole has been used to treat posttraumatic fungal keratitis caused by S apiospermum. 11 There was no such predisposing factor in our case.…”
Section: Discussionmentioning
confidence: 46%